Characterization of self-assembled protein scaffolds from collagen-mimetic peptides - Shukla D.; Lahiri J.; Parmar A.S. (My University, 2025)
Collagen-mimetic peptides have been utilized to form structures of different morphology for various biomedical and nanotechnology applications. This chapter describes the characterization of collagen-mimetic peptide self-assembled structures formed by tuning the interactions between peptides. Inclusion of varying hydrophobicity, electrostatic forces, and stereoselectivity was mainly employed in CMP designs discussed herein. The role of these forces can be assessed using multiple characterization techniques. Light scattering techniques have been employed to study the aggregation kinetics of self-assembled nanostructures and to investigate the net charge distribution of peptides. Spectroscopy techniques like circular dichroism, fluorescence, and absorption spectroscopy have been utilized to decipher the secondary structures of peptide and binding of the peptides with dyes. Imaging techniques helped in resolving the morphology of the self-assembled structures. Confocal fluorescence microscopy and differential scanning calorimetry helped in indirect assessment of hydrophobicity and X-ray studies to determine the inter-helical spacing between the triple helical peptides of the higher order structures. © Springer Science+Business Media, LLC, part of Springer Nature 2018.